Validity of the questionnaires assessing quality of life in patients with non-valvular atrial fibrillation - E. V. Minakov; S. A. Kovalev; V. N. Belov; E. A. Belova (Кардиоваскулярная терапия и профилактика, 1970)
Aim. To study the validity of Nottingham Health Profile (NHP), “Arrhythmia Patient quality of Life” (APL) scale, Duke Activity Status Index (DASI) in patients with drug-resistant atrial fibrillation (AF). Material and methods. In total, 78 patients with drug-resistant AF were examined. Later on, 54 underwent atrioventricular radio-modification or radio-ablation. Results. During functional capacity assessment in AF patients, physical stress test results and questionnaire data significantly correlated with each other. There was a positive correlation between NHP “emotional reaction”, “physical abilities”, or “energy level” domains, that might point to constructive validity of this questionnaire in AF patients. APL scale data significantly correlated with all NHP domains, as well as with functional status parameters by DASI method, that also points to sufficient validity of APL instrument in this patient group. Conclusion. NHP, DASI, and APL scale are sufficiently valid in AF patients; these methods could be used for quality of life assessment in individuals with various AF forms.